EasySTEP: A Programming Platform for the PIC16F648A Microcontroller with Applications in Educational Robotics and Automation - Souza, Vitor Amadeu (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
EasySTEP is an educational programming platform for the PIC16F648A microcontroller that allows programs written in a BASIC-like high-level language to be compiled, transmitted via RS232, and stored in the device’s internal EEPROM for interpretation by an Assembly firmware. The AutoEasy IDE supports program creation, compilation, and uploading. Nine test programs validated core functionalities including digital I/O control, iterative and conditional structures, subroutines, serial communication, PWM control, and LCD interfacing. The system targets educational robotics and low-cost automation contexts.